Evaluation of abnormal liver function tests - Limdi, J (BMJ Group, 2003)
Interpretation of abnormalities in liver function tests is a common problem faced by clinicians. This has become more common with the introduction of automated routine laboratory testing. Not all persons with one or more abnormalities in these tests actually have liver disease. The various biochemical tests, their pathophysiology, and an approach to the interpretation of abnormal liver function tests are discussed in this review.